Bounds on average and quantile treatment effects of job corps training on wages - German Blanco; Carlos A. Flores; Alfonso Flores-Lagunes (Institute for the Study of Labor (IZA), 2011)
We assess the effectiveness of Job Corps (JC), the largest job training program targeting disadvantaged youth in the United States, by constructing nonparametric bounds for the average and quantile treatment effects of the program on wages. Our preferred estimates point toward convincing evidence of positive effects of JC on wages both at the mean and throughout the wage distribution. For the different demographic groups analyzed, the statistically significant estimated average effects are bounded between 4.6 and 12 percent, while the quantile treatment effects are bounded between 2.7 and 11.7 percent. Furthermore, we find that the program's effect on wages varies across quantiles and groups. Blacks likely experience larger impacts in the lower part of their wage distribution, while Whites likely experience larger impacts in the upper part of their distribution. Non-Hispanic Females show statistically significant impacts in the upper part of their distribution but not in the lower part.
urn:nbn:de:101:1-201111072794
Keywords: J24; I38; C21; 330; training programs; wages; bounds; quantile treatment effects; Weiterbildung; Arbeitsmarktpolitik; Junge Arbeitskräfte; Wirkungsanalyse; Lohn; Schätzung; USA